Comparative evaluation of drug release from aged prolonged polyethylene oxide tablet matrices: effect of excipient and drug type. (17th February 2016) - Shojaee, Saeed; Kaialy, Waseem; Cumming, Kenneth Iain; Nokhodchi, Ali
Abstract: Polyethylene oxide (PEO) undergoes structural adjustments caused by elevated temperatures, which results in loss of its stability within direct compression tablets. The aim of this study was to evaluate the influence of filler solubility on the drug delivery process of matrix tablets containing drugs with different water-solubility properties and stored at elevated temperature. The results demonstrated that in the case of propranolol HCl (highly water-soluble) tablet matrices, soluble lactose promoted drug release, whereas, a stable release of drug was observed with insoluble DCP. A drug release pattern similar to the propranolol HCl formulation containing DCP was obtained for hydrophilic matrix tablets containing either lactose or DCP for the less water-soluble drug, zonisamide. In the case of the partially water-soluble drug, theophylline, formulated with lower molecular weight PEO 750, drug release increased considerably in the presence of both fillers with increasing storage time, however a stable release rate (similar to fresh samples) was observed in the case of higher molecular weight PEO 303 tablet matrices containing theophylline with either lactose or DCP. The hydration properties (e.g. solubility) of the diluents had a considerable effect on drug release behavior from various model matrices; this effect was dependent on both molecular weight of PEO and solubility of drug.